HUBUNGAN PERSEPSI TENTANG DUNIA KERJA DENGAN KESIAPAN MEMASUKI DUNIA KERJA MAHASISWA JURUSAN PENDIDIKAN TEKNIK INFORMATIKA DAN KOMPUTER FKIP UNIVERSITAS BUNG HATTA PADANG - Ade Fitri Rahmadani (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
This study aims to identify and disclose the relationship perceptions about the world of work with students entering the workforce readiness of the Department of Information and Computer Engineering Education Bung Hatta University in Padang. This study population is students of Department of Information and Computer Engineering Education FKIP Bung Hatta University in Padang Year Joined 2012 with a total population of 105 people. The sample in this research amounted to 53 students from the Department PTIK UBH Padang, using the formula Slovin with proportional random sampling technique. The research instrument is structured in the form of questionnaires with Likert scale model, after the tests of validity and reliability, then the data were analyzed using simple linear regression and multiple regression. The results of data analysis showed that there is a positive and significant relationship between the perception of the world of work with students entering the workforce readiness PTIK Department UBH Padang, the value of the correlation coefficient of 0.448 with a significant 0.001 <0.05. Based on the findings of this study conclude that the perception of the world of work has an important role on the readiness of students entering the work area of PTIK UBH Padang.